Impact of vitamin C deficiency on imaging patterns and ventilatory function in pulmonary tuberculosis - Cioboata, Ramona; Balteanu, Mara Amalia; Zlatian, Ovidiu Mircea; Vlasceanu, Silviu Gabriel; Driga, Mircea Vasile Popescu; Mitroi, Denisa Maria; Catana, Oana Maria; Buciu, Cezar Ionut; Camen, Georgiana; Mirea, Adina Andreea (Frontiers in Medicine, 2025)
BackgroundStudies have shown that vitamin C is essential for the immune response to tuberculosis (TB), and that its deficiency may elevate the risk of TB and related complications. This prospective study investigated the association between disease severity, imaging findings and vitamin C levels.MethodsThis study enrolled 109 patients with confirmed pulmonary tuberculosis based on Mycobacterium tuberculosis culture. Patients were divided into two groups based on serum vitamin C levels: 59 patients (54.13%) with normal levels and 50 (45.87%) with low levels.ResultsAt baseline, patients in the low vitamin C group showed significantly higher bacillar loads, with 86.00% presenting loads of 2+ or higher compared with 59.32% in the normal group (p < 0.001). After 2 months of treatment, 83.05% of the normal vitamin C group achieved culture conversion, while only 28.00% of the low vitamin C group reached the same milestone (p < 0.001). CT imaging at baseline revealed that the low vitamin C group had a significantly higher mean frequency of the tree-in-bud pattern (2.66 vs. 2.05; p < 0.001). Cavitary lesions were more prevalent in the low vitamin C group, in the superior right lobe (0.34 vs. 0.13; p = 0.011) and superior left lobe (0.34 vs. 0.14; p = 0.012). After 6 months of treatment, the low vitamin C group exhibited a higher prevalence of bronchiectasis (mean involvement in both lungs: 0.58 vs. 0.16; p < 0.001), cavitary lesions (0.32 vs. 0.00; p = 0.002), and fibrosis (0.90 vs. 0.36; p < 0.001). Pulmonary function tests showed greater impairment in the low vitamin C group. The forced expiratory volume decreased by 5.77% compared to 3.59% in the normal group (p < 0.001), the forced vital capacity (FVC) decreased by 12.00% vs. 6.67% (p < 0.001), and the Tiffeneau index by 3.34 vs. 2.13 (p = 0.002). Receiver operating characteristic (ROC) analysis indicated that FVC (AUC = 0.826) and forced expiratory flow (AUC = 0.745) were stronger predictors of treatment success in patients with normal vitamin C levels.ConclusionVitamin C deficiency is correlated with increased disease severity, delayed bacterial clearance, and persistent pulmonary damage in patients with tuberculosis. Vitamin C supplementation can enhance treatment outcomes in tuberculosis therapy.